EKSISTENSI LABORATORIUM DAKWAH DI PTKI - Nurhidayat Muhammad Said (Jurnal Dakwah Tabligh, 2016)
Dakwah Laboratory is an integral part in the implementation of teaching and learning process in the Faculty of Da'wah or Da'wah Department and is an institution that serves as the spearhead of the development of majors and courses in the Faculty of Da'wah. Dakwah Laboratory as a center of professional competence improvement of students in da'wah. Dakwah Laboratory as the center of gathering information of da'wah, both in relation to nature, character and problem faced by object of da'wah and potency which owned by ummah in supporting da'wah duty. To make themselves as the center of da'wah information, the Da'wah Laboratory should conduct da'wah research activities, so the information that is owned and developed in the training and practicum of dakwah is really based on accurate and realistic information.